Development, implementation and evaluation of the 'BELIEVE' program for improving physical activity among women: a mixed method action research study - Leila Amiri-Farahani; Soroor Parvizy; Eesa Mohammadi; Mohsen Asadi-Lari; Ziba Taghizadeh; Sally Pezaro (BMC, 2021)
Abstract Background There is insufficient physical activity among women. Yet the implementation of effective, multilevel, and evidence-based interventions may address this. Since the lifestyle of individuals is formed in many different social, physical and cultural contexts, it will be necessary in designing such interventions to involve many stakeholders. Consequently, the present study took a mixed method action research approach in developing, implementing and evaluating a bespoke program to improve physical activity among women. Methods This study was conducted within the Khoramroudi neighborhood of Tehran between 2013 and 2015 utilizing the four main phases of action research. The Mobilizing for Action through Planning and Partnerships (MAPP) process was used to design the study. During the initial phase, participants were organized into three groups; a core support committee, a steering committee, and a study population. Qualitative and quantitative data were also collected during this first phase. During the second phase, interventions were developed and implemented. In the third phase, an evaluation was carried out using both quantitative (Designing a quasi-experimental study) and qualitative methods. During the fourth phase, an exploration of the structure and process of action research was completed with the aim of providing a conceptual model and descriptions of the context. Results Three strategic interventions were effective in improving physical activity among women: (1) utilization of sports assistants; (2) Local health promotion and the dissemination of an informational, motivational and culturally competent booklet entitled "Educational content for sport assistants" (3) Group-based cognitive behavioral therapy. Quantitative results [Significant difference between the total score of PA before the intervention, and 1 and 3 months after the intervention (P < 0.001)] and the results of qualitative evaluations were shown to improve physical activity among participants. The newly co-created "adjusted MAPP model" was offered within three action cycles. The structure of this was described to capture the impacts of interactions among a variety of stakeholders. Conclusion The comprehensive identification of problems led to the development of collaborative strategies. Strategies of action research can positively affect physical activity among women. To improve physical activity outcomes more generally, the use of MAPP principles and strategies is suggested to meet the specific needs and strengths of all community members.